Improving Students' Ability in Identifying Natural Events Using the Think Pair Share Learning Model at MI Negeri 3 Musi Rawas - Purwatiningsih, Weti (MANDAILING GLOBAL EDUKASIA, 2024)
This research aims to improve students' ability to identify natural events through the implementation of the Think Pair Share (TPS) learning model at MI Negeri 3 Musi Rawas. The study was conducted with the objective of enhancing students' understanding of natural phenomena, fostering active participation, and encouraging collaborative learning in a classroom setting. The TPS model was chosen for its effectiveness in promoting peer interaction and critical thinking. This research employed a quasi-experimental design with pretest-posttest control group methodology. The sample consisted of students from the third grade of MI Negeri 3 Musi Rawas, divided into experimental and control groups. Data were collected through observation, interviews, and tests. The findings of this study indicate a significant improvement in the experimental group’s ability to identify natural events, as evidenced by the results of the posttest, which showed higher scores compared to the control group. The study concludes that the Think Pair Share model is an effective method for enhancing students' cognitive skills in understanding and identifying natural events in science education